Quantifying the evolution of animal dairy intake in humans using calcium isotopes. (15th March 2021) - Tacail, Théo; Martin, Jeremy E.; Herrscher, Estelle; Albalat, Emmanuelle; Verna, Christine; Ramirez-Rozzi, Fernando; Clark, Geoffrey; Valentin, Frédérique; Balter, Vincent
Abstract: The contribution of dairy products to modern human diets has a debated role in the expansion of Neolithic economies and the dynamics of demographic transitions. While current methods allow discussing dairy production and processing, no approach allows reconstructing quantitatively its effective consumption. Calcium isotopes (δ 44/42 Ca) potentially represent such a marker due to the abundance of isotopically fractionated Ca in dairy products. Here, we test Ca isotope sensitivity to dietary intake of dairy product: we first used a dietary model based on a compilation of available data of dietary Ca sources; we then compared the modelled outputs to available and newly acquired skeletal δ 44/42 Ca values of individuals from populations with documented and markedly distinct dairy consumption habits. Our model predicts a marked decrease of skeletal δ 44/42 Ca values with dairy Ca intake. We measure a significant difference in δ 44/42 Ca values between populations eating no dairy products and those with high proportions of dairy Ca in their diet. The average dairy Ca intakes inferred by the model agree well with the documented dietary habits of these populations. Finally, we observe a significant drift across Neolithic and Iron Age periods up to modern times in societies producing dairy, contrasting with the populations consuming no dairy products. This trend marks a dramatic change in the utilization of dietary Ca. Given the available data, our model supports a marked increase in dairy intake starting from the late Neolithic period in Western Europe. Calcium isotopes could yield significant insight into the evolutions of dairy product intakes and the biocultural revolutions experienced by Neolithic populations. Graphical abstract: Image 1 Highlights: Bone calcium isotopes can help track dairy consumption in ancient populations. Populations with distinct dairy intake habits have distinct isotope compositions. Calcium isotopes are quantitatively sensitive to the extent of dairy consumption. Calcium isotopes track changes of dairy intake from Neolithic to modern groups. Abstract : Major : Social Sciences or Biological Sciences; Minor : Anthropology.